Modern View on the Problem of Triple Negative Breast Cancer - Atakhanova N. E; Almuradova D. M; Ziyaev Sh. V (Zien Journals, 2023)
Environmental pollution, repeated artificial termination of pregnancy, and improper use of medications create conditions for the development of breast cancer (BC). According to the World Health Organization, “... throughout the world, breast cancer ranks first among malignant neoplasms in women and is characterized by high mortality. According to statistics, about 1.67 million new cases are diagnosed annually in the world, more than 571 thousand women die from breast cancer...” 1According to the literature, “...triple-negative breast cancer (TNBC) accounts for about 8-20% of all breast tumors, more often found in women before menopause, with early menarche, with the first pregnancy at an earlier age, with a short period of breastfeeding and increased body mass index ..." 2 . Frequent recurrence of the disease as a result of inadequate diagnosis and treatment, as well as the search for methods of its prevention are one of the pressing problems facing physicians.
Keywords: women; breast cancer; problems; period